2010
DOI: 10.1016/s0210-4806(10)70045-0
|View full text |Cite
|
Sign up to set email alerts
|

Blastomicosis prostática: presentación de un caso y revisión de la literatura

Abstract: Patients with Alzheimer's disease (AD) show high incidence of behavioral and psychological symptoms (BPS).The occurrence of BPS has a great impact on the patients and caregiver's quality of life, increases caregiver's burden, and in many cases precipitates admission of the patients to a geriatric center. On the other hand, the importance of the BPS is increasing because most of them are susceptible to being treated effectively, mainly thanks to the use of drug measures and behaviour modification techniques. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…Premorbid IQ has been proposed to mediate the relationship between BPSDs and cognition in AD as it significantly correlated with mood, frontal, and psychotic factors (Starr and Lonie, 2007). In a cross-sectional study, impairments in memory (episodic and semantic), executive function, and verbal fluency all correlated with the severity of neuropsychiatric symptoms (García-Alberca et al, 2010). The presence of specific neurocognitive deficits, such as executive dysfunction, was reported to predict greater BPSD symptom severity in patients with MCI, particularly of depression and anxiety (Rosenberg et al, 2011).…”
Section: Other Factors Associated With Bpsdmentioning
confidence: 99%
“…Premorbid IQ has been proposed to mediate the relationship between BPSDs and cognition in AD as it significantly correlated with mood, frontal, and psychotic factors (Starr and Lonie, 2007). In a cross-sectional study, impairments in memory (episodic and semantic), executive function, and verbal fluency all correlated with the severity of neuropsychiatric symptoms (García-Alberca et al, 2010). The presence of specific neurocognitive deficits, such as executive dysfunction, was reported to predict greater BPSD symptom severity in patients with MCI, particularly of depression and anxiety (Rosenberg et al, 2011).…”
Section: Other Factors Associated With Bpsdmentioning
confidence: 99%
“…These are known as behavioral and psychological symptoms of dementia (BPSD) and are a common motive for medical consultations, hospital admissions, and nursing home stays [1]. It is estimated that at least 90% of dementia patients will develop some type of BPSD over a period of 5 years, and this may have significant clinical implications in 85% of cases [24].…”
Section: Introductionmentioning
confidence: 99%
“…Some studies have suggested that there may be an inverse relationship, with depression present in the initial stages of the illness and absent in later ones. However, this notion may result from the difficulty in diagnosing depression in advanced stages of dementia, and not from an actual reduction in its prevalence [4]. Study of the natural history of dementia has shown that cognitive deterioration occurs more rapidly in patients with psychotic symptoms [5].…”
Section: Introductionmentioning
confidence: 99%